Initial therapeutic strategy of invasive candidiasis for intensive care unit patients: a retrospective analysis from the China-SCAN study. Issue 1 (December 2017) - Cui, Na; Wang, Hao; Su, Longxiang; Qiu, Haibo; Li, Ruoyu; Liu, Dawei
Abstract Background To investigate the impact of initial antifungal therapeutic strategies on the prognosis of invasiveCandida infections (ICIs) in intensive care units (ICUs) in China. Methods A total of 306 patients with proven ICIs in the China-SCAN study were analyzed retrospectively. Empiric, pre-emptive, and targeted therapy were adopted based on starting criteria including clinical, microbiological, and other conventional prediction rules. The primary outcome was hospital mortality and the secondary endpoints were duration days in ICU and duration days in hospital. The global responses (clinical and microbiological) at the end of the empirical therapy were also assessed. Results A total of 268/306 (87.6%) ICI patients received antifungal therapy, including 142/268 (53.0%) initial empirical therapy, 53/268 (19.8%) initial pre-emptive therapy, and 73/268 (27.2%) initial targeted therapy. Compared with the initial empirical antifungal therapy and targeted antifungal therapy, patients with initial pre-emptive antifungal therapy had significantly less clinical remission [11/53 (21.2%)vs . 61/142 (43.3%)vs . 22/73 (30.1%), P = 0.009], higher ICU [26/53 (57.8%)vs . 42/142 (32.2%)vs . 27/73 (43.5%), P = 0.008] and hospital mortality [27/53 (60.0%)vs . 43/142 (32.8%)vs . 29/73 (46.8%), P = 0.004] and more microbiological persistence [9/53 (17.0%)vs . 6/142 (4.2%)vs . 9/73 (12.3%), P = 0.011]. Kaplan-Meier survival analysis revealed that ICI patients with initial pre-emptive antifungal therapy and targeted antifungal therapy were associated with reduced hospital duration compared with patients with initial empirical antifungal therapy after confirmation of fungal infection (log-rank test:P = 0.021). Multivariate regression analysis provided evidence that initial empirical antifungal therapy was an independent predictor for DECREASING the hospital mortality in ICI patients on ICU admission and at ICI diagnosis (odds ratio 0.327, 95% confidence interval 0.160–0.667, P = 0.002; odds ratio 0.351, 95% confidence interval 0.168–0.735, P = 0.006). Conclusions The initial therapeutic strategy for invasive candidiasis was independently associated with hospital mortality. Prompt empirical antifungal therapy could be critical to decrease early hospital mortality. Trial registration Clinicaltrials.govNCT01253954 (retrospectively registration date: December 3, 2010)